Acellular and cellular high-density, collagen-fibril constructs with suprafibrillar organization. (23rd February 2016) - Blum, Kevin M.; Novak, Tyler; Watkins, Lauren; Neu, Corey P.; Wallace, Joseph M.; Bart, Zachary R.; Voytik-Harbin, Sherry L.
Abstract : Integrated use of collagen oligomers and confined compression for design of acellular and cellular high-density, collagen-fibril constructs with suprafibrillar organization. Abstract : Collagen is used extensively for tissue engineering due to its prevalence in connective tissues and its role in defining tissue biophysical and biological signalling properties. However, traditional collagen-based materials fashioned from atelocollagen and telocollagen have lacked collagen densities, multi-scale organization, mechanical integrity, and proteolytic resistance found within tissues in vivo . Here, highly interconnected low-density matrices of D-banded fibrils were created from collagen oligomers, which exhibit fibrillar as well as suprafibrillar assembly. Confined compression then was applied to controllably reduce the interstitial fluid while maintaining fibril integrity. More specifically, low-density (3.5 mg mL −1 ) oligomer matrices were densified to create collagen-fibril constructs with average concentrations of 12.25 mg mL −1 and 24.5 mg mL −1 . Control and densified constructs exhibited nearly linear increases in ultimate stress, Young's modulus, and compressive modulus over the ranges of 65 to 213 kPa, 400 to 1.26 MPa, and 20 to 150 kPa, respectively. Densification also increased construct resistance to collagenase degradability. Finally, this process was amenable to creating high-density cellularized tissues; all constructs maintained high cell viability (at least 97%) immediately following compression as well as after 1 day and 7 days of culture. This method, which integrates the suprafibrillar assembly capacity of oligomers and controlled fluid reduction by confined compression, supports the rational and scalable design of a broad range of collagen-fibril materials and cell-encapsulated tissue constructs for tissue engineering applications.